2002
DOI: 10.1161/01.str.0000021001.18101.a5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Vascular Outcome in Internal Carotid Artery Versus Middle Cerebral Artery Occlusions After Intravenous Tissue Plasminogen Activator

Abstract: Background and Purpose — Early reperfusion is a predictor of good outcome in acute ischemic stroke. We investigated whether middle cerebral artery (MCA) occlusions have a better clinical outcome and proportion of recanalization compared with internal carotid artery (ICA) occlusion after standard treatment with intravenous (IV) tissue plasminogen activator (tPA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
144
6
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(165 citation statements)
references
References 42 publications
(40 reference statements)
14
144
6
1
Order By: Relevance
“…29 Proximal clot location is increasingly appreciated as an important determinant in outcome. 3,[30][31][32] Patients with a larger clot burden have been shown to have larger infarction volumes at baseline and poorer clinical outcomes. 33,34 The CBS is designed to be weighted to vessel location, assigning higher points to the terminal ICA and proximal MCA locations.…”
Section: Discussionmentioning
confidence: 99%
“…29 Proximal clot location is increasingly appreciated as an important determinant in outcome. 3,[30][31][32] Patients with a larger clot burden have been shown to have larger infarction volumes at baseline and poorer clinical outcomes. 33,34 The CBS is designed to be weighted to vessel location, assigning higher points to the terminal ICA and proximal MCA locations.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] It was also demonstrated that early revascularization correlated very well with good clinical outcome. 6,7,17 The PROACT and PROACT II trials have shown revascularization rates of 58% and 66%, respectively, with good clinical outcomes of mRS 0 -1 at 3 months in 31% in the PROACT subjects and of mRS of 0 -2 in 40% of the PROACT II subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] However, it is likely that in certain patients, should the site of occlusion a priori be known to exist in a small branch, CDM may also help triage candidates who might benefit from systemic thrombolysis alone.…”
Section: Discussionmentioning
confidence: 99%